FACTORS INFLUENCING FINANCIAL DECISION-MAKING AND THE GENDER GAP IN FINANCIAL BEHAVIOR (American Journal of Interdisciplinary Research and Development, 2025)
Financial literacy is a critical aspect of a country's economic stability and overall development. By increasing financial literacy, we can foster economic stability and improve the personal and household well-being of the population. When people have a strong grasp of basic finances, they are better equipped to plan for retirement securely, start businesses, and invest wisely. This, in turn, fuels innovation, creates new jobs, increases money circulation, and drives economic growth. Gender gap in finances must be studied as it reveals inequalities that can be critical for economies as a whole. Numerous studies have revealed that a significant portion of women lack financial literacy and even a basic understanding of financial principles.